Differences Across Age Groups in Transgender and Gender Non-Conforming People's Experiences of Health Care Discrimination, Harassment, and Victimization. (March 2016) - Kattari, Shanna K.; Hasche, Leslie
Objective: Given the increasing diversity among older adults and changes in health policy, knowledge is needed on potential barriers to health care for transgender and gender non-conforming (GNC) individuals.Method: Using the 2010 National Transgender Discrimination Survey (NTDS), logistic regression models test differences between age groups (below 35, 35-49, 50-64, and 65 and above) in lifetime experience of anti-transgender discrimination, harassment, and victimization within health care settings while considering the influences of insurance status, level of passing, time of transition, and other socio-demographic factors.Results: Although more than one fifth of transgender and GNC individuals of all ages reported health discrimination, harassment, or victimization, significant age differences were found. Insurance status and level of passing were also influential.Discussion: Medicare policy changes and this study's findings prompt further consideration for revising other health insurance policies. In addition, expanded cultural competency trainings that are specific to transgender and GNC individuals are crucial.